408 Cases of Genital Ambiguity Followed by Single Multidisciplinary Team during 23 Years: Etiologic Diagnosis and Sex of Rearing - Georgette Beatriz De Paula; Beatriz Amstalden Barros; Stela Carpini; Bruna Jordan Tincani; Tais Nitsch Mazzola; Mara Sanches Guaragna; Cristiane Santos da Cruz Piveta; Laurione Candido de Oliveira; Juliana Gabriel Ribeiro Andrade; Guilherme Guaragna-Filho; Pedro Perez Barbieri; Nathalia Montibeler Ferreira; et al. (International Journal of Endocrinology)
Objective. To evaluate diagnosis, age of referral, karyotype, and sex of rearing of cases with disorders of sex development (DSD) with ambiguous genitalia. Methods. Retrospective study during 23 years at outpatient clinic of a referral center. Results. There were 408 cases; 250 (61.3%) were 46,XY and 124 (30.4%) 46,XX and 34 (8.3%) had sex chromosomes abnormalities. 189 (46.3%) had 46,XY testicular DSD, 105 (25.7%) 46,XX ovarian DSD, 95 (23.3%) disorders of gonadal development (DGD), and 19 (4.7%) complex malformations. The main etiology of 46,XX ovarian DSD was salt-wasting 21-hydroxylase deficiency. In 46,XX and 46,XY groups, other malformations were observed. In the DGD group, 46,XY partial gonadal dysgenesis, mixed gonadal dysgenesis, and ovotesticular DSD were more frequent. Low birth weight was observed in 42 cases of idiopathic 46,XY testicular DSD. The average age at diagnosis was 31.7 months. The final sex of rearing was male in 238 cases and female in 170. Only 6.6% (27 cases) needed sex reassignment. Conclusions. In this large DSD sample with ambiguous genitalia, the 46,XY karyotype was the most frequent; in turn, congenital adrenal hyperplasia was the most frequent etiology. Malformations associated with DSD were common in all groups and low birth weight was associated with idiopathic 46,XY testicular DSD.